The concept of neutral zone and rehabilitation of severely resorbed alveolar ridges: A special case file - K Abhay Narayane; Puttaraj T Kattimani; Krishnaraj Ranganathan; Akash Mithran; Sarathchandra Govind Raj; V Amalorpavam; Abhishek Singh Nayyar (Wolters Kluwer Medknow Publications, 2020)
Mandibular dentures often present greater difficulty in achieving retention, stability, and support than do maxillary dentures, primarily, due to a complex anatomy because of bone architecture and muscle attachments, and consequently, increased number of anatomic limitations. Long-term edentulism as well as prolonged use of ill-fitting dentures result in severe resorption of the alveolar ridges, further, worsening this situation. The present case report describes a similar case of a 90-year-old male patient who reported to the department of prosthodontics seeking replacement of his missing teeth. On examination, the lower denture was ill fitting with a severely resorbed mandibular alveolar ridge. Intraoral examination revealed an Atwood's Class III maxillary edentulous ridge with Class VI edentulous mandibular ridge. Special measures were adopted for the management of the patient through a modified impression technique along with physiologic registration of the neutral zone.